2006
DOI: 10.1111/j.1462-2920.2006.01153.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypolithic community shifts occur as a result of liquid water availability along environmental gradients in China's hot and cold hyperarid deserts

Abstract: Hypolithic cyanobacterial communities occur in hot and cold hyperarid environments but the physical factors determining their diversity are not well understood. Here we report hypolithic diversity and colonization of a common quartz substrate at several hyperarid locations in the ancient deserts of north-western China, that experience varying mean annual temperature, rainfall and concomitant availability of liquid water in soil. Microscopy and enrichment culture resulted only in Chroococcidiopsis morphotypes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
105
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(119 citation statements)
references
References 45 publications
13
105
1
Order By: Relevance
“…An implicit consequence of the classical view is that extremophilic communities could be expected to converge toward an average stable and low diversity community. Despite this, recent molecular evidence has indicated that hypolithic communities may harbor significant phylogenetic diversity among bacterial phyla (Warren-Rhodes et al, 2006;Pointing et al, 2007Pointing et al, , 2009Bahl et al, 2011). Our data demonstrate that patterns generally interpreted as indicative of the presence of niche partitioning and non-neutral processes (for example, convergence due to relatively homogeneous environments) vary on a global biogeographical scale (continent) and also between phototrophic and heterotrophic bacteria within a given community.…”
Section: Desert Microbial Community Assemblymentioning
confidence: 70%
See 3 more Smart Citations
“…An implicit consequence of the classical view is that extremophilic communities could be expected to converge toward an average stable and low diversity community. Despite this, recent molecular evidence has indicated that hypolithic communities may harbor significant phylogenetic diversity among bacterial phyla (Warren-Rhodes et al, 2006;Pointing et al, 2007Pointing et al, , 2009Bahl et al, 2011). Our data demonstrate that patterns generally interpreted as indicative of the presence of niche partitioning and non-neutral processes (for example, convergence due to relatively homogeneous environments) vary on a global biogeographical scale (continent) and also between phototrophic and heterotrophic bacteria within a given community.…”
Section: Desert Microbial Community Assemblymentioning
confidence: 70%
“…Certainly, this is partly due to the fact that we introduced the environmental effect using a relatively broad approximation (climate categories based upon long-term mean annual temperature and precipitation), which ignored any unmeasured local environmental drivers that may be involved in determining community structure (for example, see Tracy et al, 2010). However, given previous studies on these communities that showed hypoliths develop independently of the surrounding soil (Warren-Rhodes et al, 2006; Pointing et al, 2007Pointing et al, , 2009Tracy et al, 2010) owing to the specific microclimatic conditions of rocks, and that climate and continent were independent of spatial patterns observed, it is likely that a large amount of this variation is due to environmental (for example, see Dornelas et al, 2006;Pointing et al, 2009) and/or demographic stochasticity (sensu Hubbell, 2001 andTilman, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this a major gap in our understanding remains concerning the spatial distribution of desert microorganisms. Some studies on lithic communities have indicated the role of macro-climatic drivers such as mean annual precipitation including fog [13][14][15]. The influence of local scale processes has also been demonstrated, such as spatial self-organisation [15] and biological interactions [16,17].…”
Section: Introductionmentioning
confidence: 99%